Effect of single amino acid replacements on the thermal stability of the NH2-terminal domain of phage lambda repressor. - Hecht, M H (1984)
The thermal stabilities of mutant phage lambda repressors that have single amino acid replacements in the NH2-terminal domain have been studied by means of circular dichroism and differential scanning calorimetry. The variations in stability determined by these physical methods correlate with the resistance to proteolysis at various temperatures and can be compared with the temperature-sensitive activity of the mutants in vivo. In general, mutant proteins bearing solvent-exposed substitutions have thermal stabilities identical to wild type, whereas buried substitutions reduce stability. In one case, a single amino acid replacement increases the thermal stability of the repressor.